Deep brain stimulation for medically intractable cluster headache - Karl A. Sillay; Sepehr Sani; Philip A. Starr (Neurobiology of Disease, 2010)
Cluster headache is the most severe primary headache disorder known. Ten to 20% of cases are medically intractable. DBS of the posterior hypothalamic area has shown effectiveness for alleviation of cluster headache in many but not all of the 46 reported cases from European centers and the eight cases studied at the University of California, San Francisco. This surgical strategy was based on the finding of increased blood flow in the posterior hypothalamic area on H215O PET scanning during spontaneous and nitroglycerin-induced cluster headache attacks. The target point used, 4–5 mm posterior to the mamillothalamic tract, is in the border zone between posterior hypothalamus, anterior periventricular gray matter, and inferior thalamus. Recently, occipital nerve stimulation has shown efficacy, calling in question the use of DBS as a first line surgical therapy. In this report, we review the indications, techniques, and outcomes of DBS for cluster headache.